COMPETITIVE IN THE DIGITAL ERA: TRAINING ON THE USE OF E-COMMERCE TO INCREASE UMKM PRODUCTIVITY IN KADUGEDE VILLAGE - Jahidah, Nurul Siti; Adzimatinur, Fauziyah; Lesmana, Arief Surya; Pramono, Ardian Eka; Amellia, Tiara (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
The digital era has brought significant changes in the business sector, especially for Micro, Small and Medium Enterprises (MSMEs). Digital technology, especially E-Commerce platforms, is key in increasing productivity and market access for MSMEs. This community service aims to improve the ability of Micro, Small and Medium Enterprises (MSMEs) actors in Kadugede Village to use the E-Commerce platform, especially Shopee Seller. The implementation of the activity involved 10 MSME actors and consisted of four stages, namely socialisation, education, training and evaluation. The method used was Participatory Action Research (PAR). The evaluation was conducted through questionnaires and interviews before and after the training to measure the understanding and application of E-Commerce technology. The results showed that there was a significant increase in participants' understanding of the use of E-Commerce platforms, online store management, promotion strategies, and efficiency in business operations. The participants were able to increase sales by utilising the existing promotional features. In addition, the evaluation showed that participants were satisfied with the training activities. E-Commerce training in a structured and intensively assisted manner is proven to be able to improve the competitiveness of MSMEs.